2021
DOI: 10.1002/ame2.12192
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia adaptation in the cornea: Current animal models and underlying mechanisms

Abstract: Hypoxia is a state when the oxygen supply does not meet the tissue's needs. Organisms, including mammals, have developed defense mechanisms to survive hypoxia, known as hypoxia adaptation. The hypoxia adaptation process has been studied in numerous tissues and diseases, including ischemia of the heart, brain, and nearly every major organ. Besides ischemia, aggressively malignant tumor 1 and systemic hypoxic status 2 are also the focus of hypoxia adaptation research. The eyes, being a unique and important senso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 65 publications
(144 reference statements)
0
19
0
Order By: Relevance
“…As an avascular tissue, the cornea is unique in consumption by acquiring oxygen from the atmosphere and is sensitive to the oxygen concentration change (Pang et al, 2021). Hypoxia caused by the contact lens wearing, inflammation, wounds and infections, results in the disruption of corneal epithelial barrier function, delay of the wound healing, alteration of the extracellular matrix, and leads to corneal neovascularization and opacity (Lee et al, 2020;Onochie et al, 2020;Bai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As an avascular tissue, the cornea is unique in consumption by acquiring oxygen from the atmosphere and is sensitive to the oxygen concentration change (Pang et al, 2021). Hypoxia caused by the contact lens wearing, inflammation, wounds and infections, results in the disruption of corneal epithelial barrier function, delay of the wound healing, alteration of the extracellular matrix, and leads to corneal neovascularization and opacity (Lee et al, 2020;Onochie et al, 2020;Bai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia triggers a multitude of cellular and molecular changes to adapt to the lack of oxygen, particularly activating the hypoxia-inducible factor (Hif) signaling pathways 31 . While this pathway has been well studied in multiple systems, its role in the cornea is less clear 32 . In the current study, we found that alkali burn induces Hif-1α activation at 1- and 7-day post burn in the cornea and conjunctiva, and that SSOE treatment effectively inhibits this activation at 1 day but not 7-day.…”
Section: Discussionmentioning
confidence: 99%
“…From a metabolic point of view, the absence of nutrients from the blood and vitreous associated with hypoxia leads to alterations in the corneal tissues and the level of the aqueous and vitreous humor [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%